2008
DOI: 10.1121/1.2982414
|View full text |Cite
|
Sign up to set email alerts
|

Signal denoising and ultrasonic flaw detection via overcomplete and sparse representations

Abstract: Sparse signal representations from overcomplete dictionaries are the most recent technique in the signal processing community. Applications of this technique extend into many fields. In this paper, this technique is utilized to cope with ultrasonic flaw detection and noise suppression problem. In particular, a noisy ultrasonic signal is decomposed into sparse representations using a sparse Bayesian learning algorithm and an overcomplete dictionary customized from a Gabor dictionary by incorporating some a prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In the field of guided wave/ultrasonic NDT signal processing for damage or defect detection, sparse signal recovery algorithms have also attracted increasing attention during the recent decade (Hong et al, 2006;Raghavan and Cesnik, 2007;Wu et al, 2017aWu et al, , 2017bWu et al, , 2018Zhang et al, 2008). The prior information exploited in the application is that the object being inspected contains a limited amount of damage or defects, and so the measured signal should be a linear combination of echoes reflected from these damage or defects.…”
Section: Sparse Bayesian Learning and Applications In Structural Damamentioning
confidence: 99%
“…In the field of guided wave/ultrasonic NDT signal processing for damage or defect detection, sparse signal recovery algorithms have also attracted increasing attention during the recent decade (Hong et al, 2006;Raghavan and Cesnik, 2007;Wu et al, 2017aWu et al, , 2017bWu et al, , 2018Zhang et al, 2008). The prior information exploited in the application is that the object being inspected contains a limited amount of damage or defects, and so the measured signal should be a linear combination of echoes reflected from these damage or defects.…”
Section: Sparse Bayesian Learning and Applications In Structural Damamentioning
confidence: 99%
“…Our previous research showed that for the 230 MHz focused transducer, the approximate error (the root-mean squared error) using the Gabor model is smaller than 1.12% [5]. Therefore, the input displacement loads applied to the virtual transducer were modulated using the Gabor function in Eq.…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…The parameters in Eq. (2) were obtained by approximating a reference ultrasonic echo using the Gabor model as described in [5]. details can be found in [6,7].…”
Section: Finite Element Modellingmentioning
confidence: 99%
“…In order to examine the efficiency of the Gabor model for approximating ultrasonic pulses in our system, ultrasonic echoes reflected from the front surface of a steel block in a water tank were collected using the 230 MHz focused transducer in our previous study [18]. The measured echoes were then fitted by the cosine Gabor model.…”
Section: Virtual Transducer and Characterizationmentioning
confidence: 99%